The disease of subjects in societies and current concerns: anguish, stress and depression - Woloszyn, André Luís (2025)
This article discusses the discomfort of subjects over time based on the notes of Nietzsche, Freud, Bauman and Birman, relating them to the dynamics and transformations of post-contemporary society. It defends the thesis that although this sensation is of a structural nature, it has been constantly fostered by excess consumption, productivity demands and the gradual replacement of physical social relations by the digital world through social networks and games, considering them a new model of subjectivation, factors, in part, motivating anguish, stress and depression.